The giving of personal names in spoken languages and signed languages — a comparison - Philemon Akach; Johan Lubbe (Acta Academica, 2003)
This study utilises data from two Deaf communities to investigate the principles operant in the giving of personal names and to demonstrate similarities and differences as compared with those operant in spoken-language communities. Descriptive principles which operate are the physical features of the person to be named, his or her behaviour and mannerisms, associations evoked by him or her, translation of the meaning of the written name, and naming after someone else. In addition to the descriptive principles, the incorporation of the handshape of alphabetical signs is a second important principle in the giving of personal names.